Ionic Liquid Based Dispersive Liquid Liquid Microextraction and Enhanced Determination of the Palladium in Water, Soil and Vegetable Samples by FAAS - Soleiman Bahar; Razieh Zakerian (Iranian Journal of Chemistry & Chemical Engineering, 2014)
In this study, we combined Ionic Liquid-based Dispersive Liquid Liquid Micro Extraction (IL-DLLME) with FAAS for determining the palladium in different real samples at the trace level. 1-hexyl-3-methylimidazolium hexafluorophosphate [Hmim][PF6] ionic liquid and 1-(2-pyridylazo) 2-naphthol (PAN), were chosen as the extraction solvent and the chelating agent, respectively. The hydrophobic Pd–PAN complex was extracted into the [Hmim][PF6] and separated from the aqueous phase. Then, the concentration of the enriched palladium in the sediment phase was determined by FAAS. Some effective parameters that would influence the FAAS signals and the microextraction efficiency, such as concentration of the chelating agent, pH, amount of the ionic liquid, type of disperser solvent and diluting agent, ionic strength, extraction and centrifugation times were investigated and optimized. Under optimum experimental conditions, the detection limit (3s) and enhancement factor  were 3.2 μg/L and 16.2, respectively.The Relative Standard Deviation (RSD) was 1.2% at a concentration of 50 μg/L. The developed method was successfully applied for determining trace amounts of the palladium in the water, soil and vegetable samples.